Optimizing the torrefaction of pigeon pea stalk (cajanus cajan) using response surface methodology (RSM) and characterization of solid, liquid and gaseous products - Singh, R.K.; Chakraborty, J.P.; Sarkar, A. (Elsevier Ltd, 2020)
Response surface methodology was employed to determine the optimum condition for the torrefaction of pigeon pea stalk. Based on the statistical analysis, the effect of operating parameters on responses (HHV and energy yield) was temperature > residence time > heating rate. The optimum condition for maximum HHV and maximum energy yield was obtained at 248.20 °C, 60 min, and 16.03 °C/min, with desirability being 54.0%. The HHV and energy yield at optimum conditions were 21.15 MJ/kg and 78.80%, respectively. The HHV and fixed carbon increased by 25.07% and 185.86% respectively, whereas oxygen content decreased by 13.05%, at optimum condition. Scanning electron microscope and Fourier transform infrared spectroscopy analysis confirmed the effect of torrefaction on the physicochemical properties of biomass. X-ray diffraction pattern revealed a decrease in Crystallinity index value from 39.39% to 22.28% for torrefied biomass at optimum condition. Water content in the liquid products decreased with increasing severity of torrefaction. Gas chromatograph-mass spectrometry analysis confirmed the presence of phenol, furan, and ketones derivatives along with acetic acid in the liquid product obtained from torrefaction. Non-condensable gases mainly consisted of CO and CO2. At optimum condition, concentrations of H2, CO, and CO2 were 2.79, 29.78, and 67.43 vol %, respectively. © 2020 Elsevier Ltd
Keywords: Biomass; Pigeon pea stalk; Torrefaction; RSM; FTIR